Determinan Proporsi Pembiayaan Murabahah BPR Syariah - NINIK LUKIANA (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Along with the passage of time Islamic banking in Indonesia in addition to offering two products, namely financing on the basis of profit loss sharing, namely mudharabah and musyarakah (Profit Loss Sharing (PLS), also offers a more dominant product have a contribution, namely murabaha financing/Non PLS, also occurred at the Sharia Rural Banks in East Java Province. This is because the characteristics of murabaha are certain in magnitude installments and margins and can reduce the level of financing risk. The purpose of this study is to determine the factors that influence Murabahah Financing in Islamic Rural Banks in East Java Province, with the limitation of these factors are the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Non Performing Financing (NPF). This type of research is a descriptive study with a quantitative approach primary data, and the population of all Sharia Rural Banks in East Java Province recorded in the Financial Services Authority (OJK) for the 2015-2017 period, with a purposive sampling technique the amoun of samples is 26 banks. The analysis technique is multiple linear analysis, with CAR and NPF research results affecting Murabahah Financing, and FDR does not affect Murabahah Financing. His subsequent research is expected to add to the dependent and independent variables as well as the study population.